Rancang Bangun Aplikasi Dashboard Pengunjung (Studi Kasus pada Museum Teknoform Universitas Dinamika) - Kevin Surya Perdana; Sulistiowati Sulistiowati; Agus Dwi Churniawan (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2022)
Dinamika University is one of the private universities in Surabaya. Dinamika University has a museum known as the Technoform Museum. This museum is usually used as an educational facility outside the campus as well as a tourist attraction for learning Information Technology (IT). The problem so far that exists in the Technoform Museum itself is that museum staff must enter, sort and present visitor data at the Technoform Museum to make a report at the end of each month using Microsoft Excel. The sorting and presentation of the data produces detailed information including the number of visitors, the age category of visitors, the work status ofvisitors, visitor agencies, visitors from areas of origin such as visitors within Java and outside Java, employment status such as students (TK / SD / SMP / SMA / Students) and visitor agencies such as public or private schools. Therefore, the solution given is to design and build a visitor dashboard application that can make it easier for museum officers to manage, sort, present data and create reports. For presentation using descriptive statistical methods in the form of tables and graphs.